Markers of epithelial-mesenchymal transition in renal cell carcinoma - Dumanskiy, Y.V.; Kudriashov, A.G.; Vasilenko, I.V.; Kondratyuk, R.B.; Gulkov, Y.K.; Chystiakov, R.S. (Experimental Oncology, 2013)
Aim - to study the influence of markers of epithelial-mesenchymal transition (EMT) on a renal cell carcinoma (RCC) prognosis. The surgical material of 47 RCC patients who underwent nephrectomy was studied. RCC patients were distributed in two groups: a short-term survival group (3 - 6 months) and a long-term survival group (17 - 24 months). EMT markers expression was assessed by immunohistochemical methods. It was determined that the rate of spindle-cell EMT was 96,4 % in a short-term survival group and 42,1 % in a long-term survival group. High rate Furhman's nuclear atypia, i.e. degree 3 - 4 occurred in 100 % of cases in a short-term survival group versus 68,4 % in a longterm survival group. Conclusion: the rate of spindle-cell EMT in RCC may serve a more sensible prognostic factor than the degree of Furhman's nuclear atypia. Key Words: renal cell carcinoma, epithelial-mesenchymal transition, the degree of Furhman’s nuclear atypia.